Size matching in heart transplantation: Is predicted heart mass the optimal method in a United Kingdom cohort?. Issue 3 (29th December 2020) - Cheshire, Caitlin; Kydd, Anna; Nerlekar, Nitesh; Catarino, Pedro; Brown, Adam; Parameshwar, Jayan; Pettit, Stephen
Abstract: Predicted heart mass (PHM) equations have been proposed as an alternative method for size matching in heart transplantation. We assessed association between donor‐recipient size mismatch, defined using PHM equations, and survival post–heart transplant in the United Kingdom. Data from all adult patients who received a heart transplant between 1995 and 2017 were obtained from the United Kingdom Transplant Registry. PHM was calculated using published equations. Primary outcome was 1‐year survival post–heart transplantation. Recipients of undersized organs had reduced 1‐year survival (HR 1.31, 95% CI 1.03–1.67, p = .03). Oversizing had no impact on survival (HR 0.99, 95% CI 0.78–1.26, p = .96). Gender mismatching had no impact on survival in the cohort matched by PHM (HR 1.12, 95% CI 0.86–1.47, p = .4). In recipients without pulmonary hypertension, undersizing by PHM had no impact on 1‐year survival (HR 0.95, 95% CI 0.61–1.49, p = .83). In recipients with pulmonary hypertension, oversizing donor RV by using PHM RV equation (PHMRV ) results in improved survival at 1 year (HR 0.65, 95% CI 0.5–0.83, p = .001). In conclusion, receiving an organ undersized by PHM was associated with decreased 1‐year survival. Subgroup analyses demonstrated that undersizing only impacted survival in recipients with pulmonary hypertension and that these recipients had improved outcomes if they received an organ with an RV oversized by >10% by PHMRV .